Biochemistry for medical professionals - Komoda, Tsugikazu; Matsunaga, Toshiyuki (Amsterdam : Elsevier Ltd., 2015)
Biochemistry for Medical Professionals contains pivotal advances in the biochemistry field and provides a resource for professionals across medicine, dentistry, pharmaceutical sciences and health professions who need a concise, topical biochemistry reference. Relevant, well-illustrated coverage begins with the composition of the human body and then goes into the technical detail of the metabolism of the human body and biochemistry of internal organs before featuring a biotechnology study inclusive of numerous methods and applications.
Filtration in GlomeruliReabsorption in Renal Tubules; Secretion in Renal Tubules; Regulation of Humoral pH in the Kidney; Hormonal Disorders; Gastrointestinal Organs; Muscular System; References; Chapter 6 -- Biotechnological Study; Abstract; High-Performance Liquid Chromatography and High-Performance Liquid Chromatography-Mass Spectrometry; Components of High-Performance Liquid Chromatography; Chromatography Detectors; Electrospray Ionization; Fluorescence-Activated Cell Sorting; Western Blot; Northern Blot; Polymerase Chain Reaction; Relative Quantitation of Messenger RNA Expression Level
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 2, 2015).
Elsevier
Keywords: Biochemistry; Clinical biochemistry; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Biochemistry -- Handbooks, manuals, etc; Biochemistry; Medical care -- Handbooks, manuals, etc; Medical care; Biochemistry; Clinical biochemistry; Electronic books; Electronic books